Oxygen isotope composition of diatoms from Lake Emanda (northeastern Siberia, Russia) - Svetlana S Kostrova; Boris K Biskaborn; Luidmila A Pestryakova; Francisco Fernandoy; Marlene M Lenz; Hanno Meyer (PANGAEA, 2021)
The sedimentary sequence of core Co1412 from Lake Emanda (65°17'N; 135°45'E; 671 m a.s.l) has been retrieved in August 2017 using gravity and percussion piston corers (UWITEC Ltd., Austria) and investigated within the German-Russian extquotesinglePaleolimnological Transect extquotesingle (PLOT) project. Well preserved diatoms occur only in the upper 125-cm interval of a 6.1-m sediment core covering the last 13.2 cal. ka BP. Diatoms were purified to >98% SiO? and <0.8% Al?O? suitable for oxygen isotope analysis. The δ^1?O diatom values were corrected for contamination and range between +22.5 extperthousand and +27.8 extperthousand. A new dataset on diatom oxygen isotope composition provides insights into the climate and environmental dynamics in an extreme continental setting in northeastern Siberia. The δ^1?O diatom record reveals an obvious shift of 2 extperthousand in the δ^1?O diatom record at 11.7-11.5 cal. ka BP reflecting the onset of the Holocene. Relatively high δ^1?O diatom during the Early Holocene suggests relatively warm and/or dry climate with associated evaporation effects. The absolute maximum in δ^1?O diatom of +27.7 extperthousand consistent with high values of diatom indices at 7.9-7.0 cal. ka BP suggests a Mid Holocene Thermal Maximum. A continuous depletion in δ^1?O diatom since ~5.0 cal. ka BP is interpreted as Middle to Late Holocene cooling reaching the absolute minimum at 0.4 cal. ka BP (i.e. the Little Ice Age).